Effect of storage temperature and filtration on the shelf life of nypa fruticans fresh sap - Nor Fatehah Kamaruddin (School of Bioprocess Engineering, University Malaysia Perlis, 2011)
The objective of this background research is to solve the problem of lack of information about Nira, the fresh sap of nipa palm. This research was carried out to develop a procedure to improve the shelf life of Nira. The physical properties of fresh Nira and fermented sap was tested and determined. Filtration process and some test methods i.e. Brix content test (TSS) and pH measurement were conducted. Nira is filtered using 1, 2 and 3 filter papers and stored at 27C, 12.5C and -4C for 10 days. The effect on pH and dissolved solid sucrose content were determined. The results demonstrated that decreased in temperature and increased in number of filter paper during filtration process, will slow down the pH drop and increase the shelf life of Nira. This new procedure can extend the shelf life of Nira up to 10 days if it is filtered with 3 filter papers and being stored at -4C without change its natural taste.